Regulation of Peroxisome Homeostasis by Post-Translational Modification in the Methylotrophic Yeast Komagataella phaffii - Ohsawa, Shin; Oku, Masahide; Yurimoto, Hiroya; Sakai, Yasuyoshi (Frontiers in Cell and Developmental Biology, 2022)
The methylotrophic yeast Komagataella phaffii (synoym. Pichia pastoris) can grow on methanol with an associated proliferation of peroxisomes, which are subsequently degraded by pexophagy upon depletion of methanol. Two cell wall integrity and stress response component (WSC) family proteins (Wsc1 and Wsc3) sense the extracellular methanol concentration and transmit the methanol signal to Rom2. This stimulates the activation of transcription factors (Mxr1, Trm1, and Mit1 etc.), leading to the induction of methanol-metabolizing enzymes (methanol-induced gene expression) and synthesis of huge peroxisomes. Methanol-induced gene expression is repressed by the addition of ethanol (ethanol repression). This repression is not conducted directly by ethanol but rather by acetyl-CoA synthesized from ethanol by sequential reactions, including alcohol and aldehyde dehydrogenases, and acetyl-CoA synthetase. During ethanol repression, Mxr1 is inactivated by phosphorylation. Peroxisomes are degraded by pexophagy on depletion of methanol and this event is triggered by phosphorylation of Atg30 located at the peroxisome membrane. In the presence of methanol, Wsc1 and Wsc3 repress pexophagy by transmitting the methanol signal via the MAPK cascade to the transcription factor Rlm1, which induces phosphatases involved in dephosphorylation of Atg30. Upon methanol consumption, repression of Atg30 phosphorylation is released, resulting in initiation of pexophagy. Physiological significance of these machineries involved in peroxisome homeostasis and their post-translational modification is also discussed in association with the lifestyle of methylotrophic yeast in the phyllosphere.